The relationship between physical activity and food habits of students. A case study: A case study - Gheorghiu, Aurelian; Vasile, Catalin Savu; Trandafir , Marius; Serea, Cristian; Barna, Octavian (Progress in Nutrition, 2019)
The current study evaluated the relationship between physical activities and the food habits of a group of students from Galati County, in Romania. A cross-sectional study design was used to achieve the objectives. A total of 1,346 subjects, male and female students aged between 19 ± 25 years old answered a self-reported anonymous International Physical Activity Questionnaire to assess their physical activity and a self-reported anonymous Diet History Questionnaire III to establish their food habits quantified in Healthy Eating Index (HEI) 2015 score. Anthropometric measurements were used to calculate the body mass index (BMI) of the subjects. Within this study, randomly selected different subgroups of 246 subjects, also male and female students, aged between 19 ±25 years old also participated in an ancillary similar study with 1-day dietary tracking, evaluated by a dietician. The percentage of overall male students involved in intense sports activities was 28.02%, which was higher with 5.12% than the percentage of athletic female students (22.9%) tested in the main study. Median values of combined activities were expressed in metabolic equivalent task (MET)·minute/week, ranged from 421.86 MET minute/week to 5472.87 MET minute/week for male students and from 384.29 MET minute/week to 4506.62 MET minute/week for female students. For the food habits, the median values for the HEI 2015 score ranged from 51.3 to 54.7 for male students and from 52.2 to 55.3 for female students surveyed in the main study. Indices of fatness and body composition or BMI index values ranged from 24.38 to 21.18 for male students and from 23.87 to 20.64 for female students participated in the main study. The multivariate analysis of the results showed a strong correlation between a high level of physical activity and food habits. The Pearson correlation coefficient between the MET and HEI score values has the value r = 0.724 (p = 0.037) for boys students and r = 0.748 (p = 0.028) for girls tested in the main study. The statistical analysis showed that there are strong positive correlations between the indices calculated in the main study and in the ancillary study. The present study identified significant differences in the nutritional knowledge and food habits between the athletic students that had healthier food habits than non-athletic students. The results clearly support the need for developing programs for sports activity to be more accessible for everyone and better-disseminated information regarding health promotion and dietary habits, underlying the importance of prevention by a healthy behavior among students.